Analyzing Health Equity Using Household Survey Data: A Guide to Techniques and Their Implementation - Karna, Sohan Kumar (Economic Journal of Nepal, 2011)
By: Own O’Donnel, Eddy Van Doorslaer, Adam Wagstaff and Magnus Lindelow (2008).